Reproductive Health Literacy Among Female Adolescents in Banda Aceh: A Descriptive Study - Yusuf, Wardiati; Septiani, Riza; Ariscasari, Putri; Mairani, Tiara; Arlianti, Nopa; Naimah, Naimah; Menawati, Menawati; Mira Gusweni; Irma Hamisah; Stefany Fellyciani Ina Aran (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Reproductive Health Literacy (RHL) has been identified as a key factor in adolescent reproductive health problems because it plays a vital role in promoting overall well-being. However, limited research has been conducted to explore this topic in Indonesia. This study aimed to measure the RHL level of female adolescents in Banda Aceh, Indonesia. Method: This study employed a descriptive cross-sectional design with 694 respondents from four randomly selected schools. Participants were chosen using a convenience sampling technique based on their willingness to participate. Data was collected through self-reported questionnaires. Result: The study found that two-thirds of the respondents had adequate RHL level. However, 20.5% had problematic levels of understanding reproductive health information, and 28.1% had an issue applying this information. Conclusion: While most respondents possessed sufficient RHL, a significant proportion struggled to judge and apply reproductive health information. Therefore, the Health Office of Banda Aceh City should develop health promotion programs to help adolescents improve their ability to assess and make informed decisions related to reproductive health.